A highly breathable adhesive tape and its preparation method and application

By using a highly breathable tape composed of a porous substrate and a highly permeable pressure-sensitive adhesive layer in lithium batteries, the problem of poor ion permeability of existing tapes is solved, and the good shuttle of lithium ions and the safety performance of the battery is improved.

CN118325498BActive Publication Date: 2025-03-18STEADYCHEM (SHANGHAI) CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410548019.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-06
Publication Date
2025-03-18
Estimated Expiration
2044-05-06

AI Technical Summary

Technical Problem

When used at the corners of the battery cell, the existing electrolyte-resistant lithium battery separator tape has poor ion permeability, which leads to the inability to pass through the lithium ions, causing the risk of reducing the battery's electrical performance and safety.

Method used

A porous substrate and a highly permeable pressure-sensitive adhesive layer are used to combine porous and/or composite fillers to form a highly breathable tape, which improves the initial and bubble permeability of the tape, ensures the shuttle of lithium ions, and provides sufficient bonding strength and toughness.

Benefits of technology

It achieves sufficient ion permeability during the battery cycle, prevents defects such as lithium excretion, extends the service life of the battery, and protects the electrode sheet from cracking during the hot pressing process, improving the pass rate of the battery product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118325498B_ABST
    Figure CN118325498B_ABST
Patent Text Reader

Abstract

A highly air-permeable adhesive tape and a preparation method and application thereof, the adhesive tape comprising a porous substrate and a pressure-sensitive adhesive layer; the porous substrate has a thickness of 5-50 μm and is selected from at least one of a porous polymer diaphragm and a non-woven fabric; the pressure-sensitive adhesive layer has a thickness of 0.5-50 μm and comprises at least one raw material composition of composition (1) or composition (2): composition (1) comprises: 20-45% of a rubber component, 5-25% of a viscosity modifier, 30-75% of a filler, and optionally a tackifying resin and a carbonate compound; composition (2) comprises: 20-70% of a hydroxyl / carboxyl-terminated acrylate resin, 1-10% of a curing agent, 25-75% of a filler, and optionally a carbonate compound; the filler particle size is 1 nm-15 μm; the initial air permeability of the adhesive tape is less than 350 s / 100 cc, and the air permeability after being immersed in an electrolyte is less than 370 s / 100 cc, and the tape has good ion permeability and stable bonding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery tapes, and in particular relates to a highly breathable tape and a preparation method and application thereof. Background Art

[0002] In the normal production process of lithium batteries, the positive electrode sheets are wound with the separator and the negative electrode sheets, and then undergo processes such as hot pressing, liquid injection, and chemical formation to prepare the battery cells. Since the electrode sheets are somewhat brittle, the bending amplitude of the electrode sheets wound in the inner layer of the battery cells is often large at the corners of the battery cells, and there is a large stress, which leads to easy cracking after hot pressing, and the active material falls off, thus affecting the yield rate and safety of the battery cells, or causing lithium deposition at the corners during the battery cycle, and causing the wound battery cells to deform, so that the electrode sheets at the corners are at risk of breaking, affecting the safety performance and cycle performance of the battery.

[0003] Pasting tape on the pole piece at the corresponding position can effectively prevent the pole piece from hot pressing cracking, lithium deposition at the corner of the battery cell, deformation and fracture of the battery cell. Using flexible substrate tape can prevent the cracking of the tape substrate. The tape used in conventional lithium batteries is generally electrolyte-resistant, and the adhesive used in the glue layer is generally acrylic pressure-sensitive adhesive, hot melt adhesive, etc. The substrate is generally PET, BOPP film, etc. These types of tapes have low solubility in the electrolyte and are not permeable to lithium ions, which limits their use in the corners inside the battery cell.

[0004] Invention CN117363229A discloses an electrolyte-resistant lithium battery special-shaped tape and a preparation method thereof, wherein the tape comprises a three-dimensional base layer, and the base layer comprises effective ingredients by weight: 50-80 parts of natural rubber; 12-20 parts of styrene-butadiene rubber; 7-10 parts of TPI; 4-7 parts of acrylic staple fibers; 7-10 parts of micron filler; and 32-45 parts of functional additives. In the invention, fillers are added and a three-dimensional base layer is used to prepare the tape, thereby improving the adhesion and corrosion resistance to irregular shapes. However, if the tape is used at locations such as the corners of a battery cell, the tape has a dense structure and poor ion permeability, which will prevent lithium ions from passing through and lithium ion precipitation will occur at the edge of the tape, causing the risk of reduced electrical performance and safety of the battery.

[0005] Invention CN115651554A discloses a battery separator tape with a soluble adhesive layer and a preparation method thereof. The battery separator tape includes a battery separator and an adhesive layer disposed on the surface of the battery separator. The adhesive forming the adhesive layer includes the following raw materials in weight percentage: 40-60% solvent-based polyacrylate; 10-30% polyvinyl acetate; 5-15% polystyrene resin; 0.1-0.5% initiator; 0.5-1.0% curing agent; 0-30% solvent. The adhesive layer of the battery separator tape provided by the invention can be quickly and basically completely dissolved in the electrolyte, and will not block the normal migration of lithium ions. However, the separator matrix used therein still has the problems of insufficient porosity and poor ion permeability. The tape still has the risk of falling off after the adhesive layer is dissolved, and basically cannot reflect the bonding performance. Overall, the tape has the risk of falling off in the subsequent battery cycle after it is dissolved, and the problem of lithium precipitation cannot be avoided.

[0006] Therefore, how to select the existing electrolyte-resistant battery separator tape materials and structures to provide sufficient bonding strength and toughness to protect the pole pieces from cracking under stress during the hot pressing process, and to provide sufficient ion permeability during the battery cycle to prevent defects such as pole piece deformation caused by battery lithium deposition has become an urgent problem to be solved by technical personnel in this field. Summary of the invention

[0007] To solve the above problems, the present invention provides a highly breathable adhesive tape and a preparation method and application thereof. The highly breathable adhesive tape is formed by using a porous substrate and a highly permeable pressure-sensitive adhesive layer, which is particularly suitable for lithium batteries, providing excellent initial and bubble liquid permeability, and providing sufficient ion permeability during the battery cycle to prevent defects such as lithium precipitation. In addition, the adhesive tape of the present invention has sufficient and stable bonding strength and toughness, and protects the pole piece from cracking under stress during the hot pressing process.

[0008] In a first aspect, the present invention provides a highly breathable adhesive tape, comprising a porous substrate and a pressure-sensitive adhesive layer;

[0009] The porous substrate has a thickness of 5-50 μm and is selected from at least one of a porous polymer membrane and a non-woven fabric;

[0010] The thickness of the pressure-sensitive adhesive layer is 0.5-50 μm, and the pressure-sensitive adhesive layer comprises at least one of the raw materials in composition (1) or composition (2):

[0011] In terms of weight percentage, the composition (1) includes: 20-45% of a rubber component, 5-25% of a viscosity modifier, 30-75% of a filler, and optionally a tackifying resin and a carbonate compound;

[0012] In terms of weight percentage, composition (2) includes: 20-70% of a hydroxyl / carboxyl terminated acrylate resin, 1-10% of a curing agent, 25-75% of a filler, and optionally a carbonate compound;

[0013] The filler includes a filler with a particle size of 1nm-15μm;

[0014] The initial air permeability of the highly breathable tape is less than 350s / 100cc, and the air permeability after being soaked in electrolyte is less than 370s / 100cc.

[0015] The present invention uses a porous substrate, a high-permeability pressure-sensitive adhesive layer, etc. to form a highly breathable tape. On the one hand, the porous substrate is used to provide good and long-term basic permeability, and the overall ion permeability and bonding performance of the tape are optimized by adjusting the raw material composition of the pressure-sensitive adhesive layer; on the other hand, the filler's physicochemical properties and structural characteristics are used to form a gap between the filler and the resin matrix to further increase the overall permeability of the tape. The filler of the present invention does not need to be surface treated, and there is no need to specifically improve its compatibility with the resin matrix. It can be seen that the way the present invention uses fillers to increase the air permeability of the tape is significantly different from the uses and effects of traditional fillers such as reinforcement, insulation / conductivity, etc.

[0016] Preferably, the porous polymer membrane is selected from at least one of a porous PP membrane, a porous PE membrane, a porous PI membrane, a porous PAN membrane, a porous PVDF membrane, and a porous PMMA membrane, and has a porosity of 30-85%;

[0017] The non-woven fabric includes at least one of PP non-woven fabric, PE non-woven fabric, PET non-woven fabric and PTFE non-woven fabric, and the pore size is ≤10um.

[0018] The aforementioned porous substrate can provide sufficient strength for the tape while maintaining good air permeability. The air permeability of the substrate of the present invention is below 350s / 100cc, preferably below 280s / 100cc, and more preferably below 240s / 100cc.

[0019] Preferably, the filler is selected from at least one of boehmite, talc and silicon dioxide. The filler comprises a porous filler with a specific surface area of ​​2 m 2 / g or more, preferably 10m 2 / g or more, preferably with a particle size of 10nm-10μm; and / or a composite filler, using a small particle size filler with a particle size of 1-600nm and a large particle size filler with a particle size of 700nm-15μm, preferably 700nm-10μm, in a weight ratio of (20-40): (60-80).

[0020] On the basis of using fillers to increase air permeability, the present invention screens out more preferred filler types and usage methods. First, the above-mentioned filler types make the compatibility between the filler and the resin poor, and a large number of gaps are conducive to the formation of continuous channels. The above-mentioned fillers can be commercially available products, which can be further screened according to the particle size requirements. Secondly, when using porous fillers, the porous structure inherent in the filler can form an air-permeable channel; when using a composite filler with a non-porous structure, the surface roughness of the filler and the poor resin infiltration are utilized to form gaps on the surface. At the same time, the filler with a small particle size is filled in the gaps between the fillers with a large particle size to connect the channels. The above two fillers can also be further compounded and used, that is, a large-particle porous filler and a small-particle porous filler are compounded.

[0021] Optionally, the pressure-sensitive adhesive layer is patterned and covered on the surface of the porous substrate, and the coverage area accounts for 10-50% of the total area of ​​the porous substrate, preferably 20-40%. The patterned covering method is used to reduce the coverage area, which is conducive to further improving the overall air permeability of the tape.

[0022] Specifically, although the material selection of the pressure-sensitive adhesive layer of the present invention is not unique, the following two compositions are preferably obtained based on comprehensive conditions such as bonding performance, air permeability, and compliance with the internal use requirements of lithium batteries:

[0023] The first type, in terms of weight percentage, comprises:

[0024]

[0025] The rubber component is selected from at least one of SIS, SEBS, SEPS, SBr, and TPU; preferably, the styrene content in SIS, SEBS, SEPS, and SBr is ≤40wt%;

[0026] The viscosity modifier is selected from at least one of liquid polyolefin and naphthenic mineral oil;

[0027] The tackifying resin is selected from at least one of (hydrogenated) C5 resin, (hydrogenated) C9 resin, and (hydrogenated) DCPD resin.

[0028] The second type, in terms of weight percentage, comprises:

[0029]

[0030] The molecular weight of the hydroxyl / carboxyl terminated acrylate resin is 20,000-500,000 Da;

[0031] The curing agent is selected from at least one of multifunctional epoxy and multifunctional isocyanate.

[0032] The hydroxyl / carboxyl terminated acrylate resin can be prepared by a thermal initiation method or a photoinitiation method. The hydroxyl terminated acrylate monomer is selected from one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, propyl methacrylate, hydroxybutyl acrylate, and hydroxybutyl methacrylate. The carboxyl terminated acrylate monomer is selected from at least one of acrylic acid and methacrylic acid.

[0033] Preferably, the content of the carbonate compound is 10-20%, and is selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, and methyl propyl carbonate. Currently, the electrolyte solvents used in lithium-ion batteries mainly include carbonate solvents such as dimethyl carbonate, ethylene carbonate, and ethyl methyl carbonate. A small amount of carbonate compound added is easy to dissolve in the electrolyte, increases the swelling channel of the adhesive layer, and is conducive to regulating the swelling rate / time, dissolution rate / time, etc. of the pressure-sensitive adhesive layer.

[0034] In a second aspect, the present invention provides a method for preparing a highly breathable adhesive tape, comprising the following steps:

[0035] Step 1: Prepare the pressure-sensitive adhesive coating liquid:

[0036] Weigh each component according to the raw material composition, and mix each component with the solvent to obtain a coating liquid;

[0037] Step 2: Coating and film forming:

[0038] The coating liquid is coated on a porous substrate, and dried to form a pressure-sensitive adhesive layer to obtain a highly breathable adhesive tape; or

[0039] The coating liquid is first coated on a release film, and after drying, is transferred to a porous substrate to form a pressure-sensitive adhesive layer to obtain a highly breathable adhesive tape;

[0040] Step 3: Tape Rewinding:

[0041] A release agent is coated on the back of the porous substrate or a release film is arranged on the surface of the pressure-sensitive adhesive layer, and the tape is rolled up to produce a single-sided rolled high-air-permeable tape.

[0042] Preferably, the solvent is an organic solvent, including at least one of toluene, xylene, methylcyclohexane, ethyl acetate, butyl acetate, butanone, methyl isobutyl ketone, ethanol and isopropanol, and the solid content of the coating liquid is 5-60wt%.

[0043] In a third aspect, the present invention provides an application of the aforementioned highly breathable adhesive tape in the protection of lithium battery pole pieces, pole tabs, and winding and finishing.

[0044] The present invention has at least the following beneficial effects:

[0045] (1) The present invention prepares a highly breathable tape by laminating a pressure-sensitive adhesive layer on a porous substrate. During the application process such as electrode winding, the tape provides sufficient mechanical strength and support for the electrode. In the subsequent hot pressing process, the electrode is protected from cracking, thereby improving the qualified rate of battery products.

[0046] (2) The present invention adopts a porous substrate, a high-permeability pressure-sensitive adhesive layer, and uses porous and / or composite fillers, which can form a large number of air permeable channels in the components themselves and between the components, without affecting the shuttling of lithium ions, providing the tape with initial and long-term stable air permeability, which is beneficial to improving the battery energy density.

[0047] (3) During the battery cycle, the tape at the corners of the battery cell has excellent lithium ion transmittance, which can avoid defects such as lithium deposition at the corners of the battery cell and deformation of the battery cell, thereby extending the service life of the battery.

[0048] (4) By setting the pattern of the porous substrate and the pressure-sensitive adhesive layer, selecting the filler, adding carbonate compounds, etc., multiple parameters of the tape such as the foam swelling rate / time, dissolution rate / time, air permeability, and peel strength can be adjusted to meet various application requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a schematic structural diagram of the highly breathable adhesive tape of the present invention.

[0050] Reference numerals: 1 - pressure-sensitive adhesive layer, 2 - porous substrate. DETAILED DESCRIPTION

[0051] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.

[0053] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.

[0054] See also Figure 1 The present invention provides a highly breathable adhesive tape with stable adhesive force, comprising a porous substrate 2 and a pressure-sensitive adhesive layer 1, wherein the initial air permeability of the adhesive tape is less than 350s / 100cc, and the air permeability after soaking in electrolyte is less than 370s / 100cc. Soaking in electrolyte comprises: placing the adhesive tape in a container filled with electrolyte solvent and submerging the tape above the liquid surface, sealing the container and baking it at 80-90°C for 20-30hrs, then taking it out and wiping off the surface solvent. The electrolyte solvent components and mass ratios are diethyl carbonate DEC: ethylene carbonate EC: ethyl methyl carbonate EMC = (30-70): (10-50): (10-40), preferably, the specific components and mass ratios of the electrolyte solvent are: diethyl carbonate DEC: 50%, ethylene carbonate EC: 30%, ethyl methyl carbonate EMC: 20%.

[0055] 1. A porous substrate 2, with a thickness of 5-50 μm, selected from at least one of a porous polymer membrane and a non-woven fabric, wherein the air permeability of the porous substrate 2 is less than 350 s / 100 cc, preferably less than 280 s / 100 cc, and more preferably less than 240 s / 100 cc:

[0056] The porous polymer separator is selected from at least one of a porous PP film, a porous PE film, a porous PI film, a porous PAN film, a porous PVDF film, and a porous PMMA film, with a porosity of 30-85%;

[0057] The non-woven fabric includes at least one of PP non-woven fabric, PE non-woven fabric, PET non-woven fabric and PTFE non-woven fabric, and the pore size is ≤10um.

[0058] 2. A pressure-sensitive adhesive layer 1 having a thickness of 0.5-50 μm, the pressure-sensitive adhesive layer 1 can completely cover the porous substrate 2, see Figure 1 ; It can also be patterned and laminated on the porous substrate 2, for example, the coverage area accounts for less than 50% of the total area of ​​the porous substrate 2, preferably 10-50%, more preferably 20-40%;

[0059] The invention comprises at least one raw material composition of composition (1) or composition (2):

[0060] Composition (1), by weight percentage, comprises: 20-45% of a rubber component, 5-25% of a viscosity modifier, 30-75% of a filler, and optionally a tackifying resin and a carbonate compound;

[0061] Preferably, it includes:

[0062]

[0063] (1.1) The rubber component is selected from at least one of SIS, SEBS, SEPS, SBr, and TPU; preferably, the styrene content in SIS, SEBS, SEPS, and SBr is ≤40wt%;

[0064] (1.2) The viscosity modifier is selected from at least one of liquid polyolefin and naphthenic mineral oil;

[0065] (1.3) The tackifying resin is selected from at least one of (hydrogenated) C5 resin, (hydrogenated) C9 resin, and (hydrogenated) DCPD resin.

[0066] Composition (2), in terms of weight percentage, comprises: 20-70% of a hydroxyl / carboxyl terminated acrylate resin, 1-10% of a curing agent, 25-75% of a filler, and optionally a carbonate compound;

[0067] Preferably, it includes:

[0068]

[0069] (2.1) The molecular weight of the hydroxyl / carboxyl terminated acrylate resin is 20,000-500,000 Da;

[0070] (2.2) The curing agent is selected from at least one of a multifunctional epoxy and a multifunctional isocyanate.

[0071] The hydroxyl / carboxyl terminated acrylate resin can be prepared by a thermal initiation method or a photoinitiation method.

[0072] The thermal initiation method is used to prepare a hydroxyl / carboxyl terminated acrylate resin, comprising:

[0073] I) heating the reactor to 40-50° C., adding 3-6 parts of acrylate prepolymer, 80-120 parts of common acrylate monomer, and 140-160 parts of solvent by weight, and stirring at 30-60 rpm for 30-90 min;

[0074] II) heating to 55-65°C and passing nitrogen, then adding dropwise a portion (about 5-8 parts, accounting for 50-65% of the total solution) of a thermal initiator solution (solid content 0.5-1.5 wt%) and

[0075] 140-150 parts of solvent, stirring at 20-60 rpm for at least 4 hours;

[0076] III) When the viscosity reaches 9,000±200cps and the molecular weight reaches 12,000±300Da, add another portion (about 2-4 parts, accounting for 25-35% of the total solution) of thermal initiator solution and 140-155 parts of solvent, raise the temperature to 70-75°C and continue the reaction for at least 3 hours;

[0077] IV) when the viscosity and molecular weight reach the requirements (e.g., the viscosity reaches 14,000±200cps, the molecular weight reaches 40,000±300Da), add the remaining thermal initiator solution (about 0.5-1.5 parts, accounting for 10-15% of the total solution), 145-155 parts of solvent and 1-3 parts of end-capping acrylate monomer, and react for 3-5 hours;

[0078] V) Discharge the material when the viscosity and molecular weight reach the requirements (for example, the viscosity reaches 20,000±200cps, and the molecular weight reaches 50,000±300Da).

[0079] The photoinitiator method is used to prepare a hydroxyl / carboxyl terminated acrylate resin, comprising:

[0080] I) adding 3-6 parts of acrylate prepolymer, 80-120 parts of common acrylate monomer and 140-160 parts of solvent into a reaction kettle, and stirring at a speed of 30-60 rpm for 30-90 min;

[0081] II) nitrogen is passed through, and then a portion (about 4-6 parts, accounting for 45-55% of the total solution) of photoinitiator solution (solid content 0.5-1.5wt%) and 140-150 parts of solvent are added, and stirred at 20-40rpm for at least 30min;

[0082] III) Use ultraviolet light (e.g. LED 365nm wavelength) to irradiate the side wall of the reactor at a distance of 10±1cm and a power of 5-15mW / cm 2 When the viscosity reaches 9,000±200cps and the molecular weight reaches 12,000±300Da, add another portion (about 3-5 parts, accounting for 35-45% of the total solution) of photoinitiator solution and 140-150 parts of solvent, and increase the speed to 55-65rpm;

[0083] IV) when the viscosity and molecular weight reach the requirements (e.g., the viscosity reaches 14,000±200cps, and the molecular weight reaches 40,000±300Da), add the remaining photoinitiator solution (about 0.5-1.5 parts, accounting for 10-20% of the total solution), 145-155 parts of solvent, and 1-3 parts of end-capping acrylate monomer;

[0084] V) When the viscosity and molecular weight meet the requirements (for example, the viscosity reaches 20,000 ±

[0085] 200cps, molecular weight reaches 50,000±300Da), stop irradiation and discharge.

[0086] Among them, the acrylate prepolymer is preferably a bifunctional acrylate prepolymer: epoxy-modified polyurethane, polyether polyurethane, polyester polyurethane and polycarbonate polyurethane acrylate resin, etc., with a molecular weight of 2,000-6,000Da;

[0087] Photoinitiator: 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1-hydroxycyclohexyl phenyl ketone, α,α-dimethoxy-α-phenylacetophenone, 2,4-dihydroxybenzophenone, etc. The amount of photoinitiator added is 0.1%-0.5% of the total mass of the prepolymer and the monomer.

[0088] Thermal initiator: azobisisobutylnitrile, azobisisoheptylnitrile, dimethyl azobisisobutyrate, dibenzoyl peroxide, di-tert-butyl peroxide, diisopropylbenzene peroxide, tert-butyl perbenzoate, tert-butyl peroxyvalerate, etc. The amount of thermal initiator added is 0.1%-0.5% of the total mass of the prepolymer and the monomer.

[0089] Common acrylate monomers: tricyclodecane dimethanol diacrylate, triethylene glycol acrylate, triethylene glycol dimethacrylate, ethoxylated bisphenol A acrylate, ethoxylated bisphenol A dimethacrylate, propoxylated neopentyl glycol diacrylate.

[0090] Acrylate monomers for hydroxyl termination: one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, propyl methacrylate, hydroxybutyl acrylate, and hydroxybutyl methacrylate.

[0091] Acrylate monomer for carboxyl end-capping: at least one of acrylic acid and methacrylic acid.

[0092] Solvents: ethyl acetate, butyl acetate, toluene, methyl isobutyl ketone, butanone, etc.

[0093] In composition (1) and composition (2), preferably, the content of the carbonate compound is 10-20%, and is selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, and methylpropyl carbonate.

[0094] The aforementioned filler is at least one selected from boehmite, talc, and silicon dioxide, and is in the form of a porous filler and / or a composite filler;

[0095] Porous filler, porosity above 20%, specific surface area above 2m2 / g or more, preferably 10m 2 / g or more, preferably with a particle size of 10nm-10μm; more preferably, a boehmite porous filler is used, with a D10 of 10nm-2μm, a D50 of 50nm-3μm, and a D90 of 100nm-5μm;

[0096] The composite filler is a small-particle filler with a particle size of 1-600 nm and a large-particle filler with a particle size of 700 nm-15 μm, preferably 700 nm-10 μm, in a weight ratio of (20-40): (60-80). The small-particle filler and the large-particle filler can be the same or different, and the composite filler can also be a porous filler.

[0097] The preparation method of the highly breathable adhesive tape comprises the following steps:

[0098] Step 1: Prepare the coating liquid for the pressure-sensitive adhesive layer 1:

[0099] Weigh each component according to the raw material composition, and mix each component with a solvent to obtain a coating liquid; the solvent is an organic solvent selected from at least one of toluene, xylene, methylcyclohexane, ethyl acetate, butyl acetate, butanone, methyl isobutyl ketone, ethanol, and isopropanol, and the solid content of the coating liquid is 5-60wt%.

[0100] Step 2: Coating and film forming:

[0101] The coating liquid is coated on a porous substrate 2 and dried to form a pressure-sensitive adhesive layer 1, thereby obtaining a highly air-permeable adhesive tape.

[0102] Alternatively, the coating liquid is first coated on a release film, and then transferred to the porous substrate 2 after drying to form a pressure-sensitive adhesive layer 1 to obtain a highly breathable adhesive tape. The performance of the product obtained in this way is basically similar to that of the above-mentioned direct coating method.

[0103] When the pressure-sensitive adhesive layer 1 is patterned and covered on the surface of the porous substrate 2, the coating liquid can be coated on the porous substrate 2 and dried to obtain a certain pattern, or coated on a release film to obtain a certain pattern, and after drying, the pattern on the release film is transferred to the porous substrate 2.

[0104] Step 3: Tape Rewinding:

[0105] A release agent is coated on the back of the porous substrate 2 or a release film is provided on the surface of the pressure-sensitive adhesive layer 1, and the tape is rolled up to prepare a single-sided rolled high-air-permeable tape.

[0106] The high-permeability adhesive tape of the present invention has an initial air permeability of less than 350s / 100cc, and an air permeability of less than 370s / 100cc after being soaked in electrolyte. Moreover, before and after being soaked in electrolyte, the peel strength decreases by less than 15%, preferably less than 10%, and has high adhesion and electrolyte stability, thus ensuring long-term stable use of the adhesive tape in batteries.

[0107] The raw materials used in the following examples are shown in Table A, which is only used as a reference and is not intended to limit the present invention.

[0108] Table A

[0109]

[0110]

[0111] 1. Prepare hydroxyl-terminated acrylate resin by thermal initiation method, including:

[0112] I) heating the reactor to 45° C., adding 5 parts of polyurethane acrylate prepolymer (molecular weight about 5,000 Da, brand UN-9000PEP), 100 parts of tricyclodecane dimethanol diacrylate monomer (brand SR833s), and 150 parts of ethyl acetate, by weight, and stirring at 45 rpm for 60 min;

[0113] II) heating to 60°C and passing nitrogen, then dropping part (about 6 parts, accounting for 60% of the total solution) of thermal initiator solution (solid content 1.0wt%) and 150 parts of ethyl acetate, stirring at 45rpm for 5 hours; the thermal initiator is azobisisobutyronitrile, and the addition amount is 0.2% of the total mass of the prepolymer and the monomer;

[0114] III) When the viscosity reaches 9,000±100cps and the molecular weight reaches 12,000±150Da, add another portion (about 2.5 parts, accounting for 25% of the total solution) of thermal initiator solution and 150 parts of ethyl acetate, raise the temperature to 70°C and continue the reaction for 4 hours;

[0115] IV) When the viscosity reaches 14,000±100cps and the molecular weight reaches 40,000±150Da, add the remaining thermal initiator solution (about 1.5 parts, accounting for 15% of the total solution), 150 parts of ethyl acetate and 2 parts of hydroxyethyl acrylate monomer for end-capping, and react for 4 hours;

[0116] V) When the viscosity reaches 200,000±100cps and the molecular weight reaches 310,000±150Da, the material is discharged.

[0117] 2. Self-made carboxyl-terminated acrylate resin by photoinitiation method, including:

[0118] I) 5 parts of polyurethane acrylate prepolymer (molecular weight about 5,000Da, brand UN-9000PEP), 100 parts of tricyclodecane dimethanol diacrylate monomer, and 150 parts of ethyl acetate were stirred at 45 rpm for 60 minutes;

[0119] II) nitrogen was passed through, and then part (about 5 parts, accounting for 50% of the total solution) of photoinitiator solution (solid content 1.2wt%) and 150 parts of ethyl acetate were added, and stirred at 30rpm for 45min; the photoinitiator was 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and the amount added was 0.25% of the total mass of the prepolymer and the monomer;

[0120] III) Use LED 365nm wavelength ultraviolet light to irradiate the side wall of the reactor at a distance of 10±1cm and a power of 10mW / cm 2 When the viscosity reaches 9,000±100cps and the molecular weight reaches 12,000±150Da, add another portion (about 4 parts, accounting for 40% of the total solution) of photoinitiator solution and 150 parts of ethyl acetate, and increase the speed to 60rpm;

[0121] IV) When the viscosity reaches 14,000±100cps and the molecular weight reaches 40,000±150Da, add the remaining photoinitiator solution (about 1.0 part, accounting for 10% of the total solution), 150 parts of ethyl acetate, 1 part of acrylic acid monomer for end-capping, and 1 part of methacrylic acid monomer;

[0122] V) When the viscosity reaches 200,000±100 cps and the molecular weight reaches 320,000±150 Da, stop irradiation and discharge the material.

[0123] Preparation Example 1:

[0124] The preparation method of the highly breathable tape sample comprises the following steps:

[0125] Step 1: Prepare the pressure-sensitive adhesive coating liquid:

[0126] Weigh each component according to the raw material ratio of composition (1), and mix each component with a solvent to obtain a coating liquid; the solvent is toluene, and the solid content of the coating liquid is 15%;

[0127] Step 2: Coating and film forming:

[0128] The coating liquid is first coated on a release film, and after drying, is transferred to a porous PP film substrate to form a pressure-sensitive adhesive layer to obtain a highly breathable adhesive tape;

[0129] Step 3: Tape Rewinding:

[0130] A release agent is applied to the back of the porous PP film and the tape is rolled up to produce a single-sided highly breathable tape.

[0131] Preparation Example 1 corresponds to the samples of Examples 1-1 to 1-11, wherein the porosity of the porous PP film is 45±10%;

[0132] Comparative Examples 1-1, 1-2 and 1-3:

[0133] The difference between Comparative Example 1-1 and Example 1-3 is that no filler is used;

[0134] The difference between Comparative Example 1-2 and Example 1-3 is that the amount of filler is increased, and the weight percentage of the filler is about 75.8% after conversion;

[0135] The difference between Comparative Example 1-3 and Example 1-3 is that only filler XH-SiO2-800 is used. Specific parameters are shown in Tables 1-1-1 and 1-1-2:

[0136] Table 1-1-1

[0137]

[0138]

[0139] Table 1-1-2

[0140]

[0141] Preparation Example 2:

[0142] The preparation method of the highly breathable tape sample comprises the following steps:

[0143] Step 1: Prepare the pressure-sensitive adhesive coating liquid:

[0144] Weigh each component according to the raw material ratio of composition (1), and mix each component with a solvent to obtain a coating liquid; the solvent is toluene, and the solid content of the coating liquid is 15%;

[0145] Step 2: Coating and film forming:

[0146] The coating liquid is first coated on a release film, and after drying, is transferred to a PP non-woven fabric substrate to form a pressure-sensitive adhesive layer to obtain a highly breathable adhesive tape;

[0147] Step 3: Tape Rewinding:

[0148] A release agent is applied to the back of the PP nonwoven fabric and the tape is rolled up to produce a single-sided, highly breathable tape.

[0149] Preparation Example 2 corresponds to samples of Examples 1-12 to 1-18;

[0150] Comparative Examples 1-4, 1-5 and 1-6:

[0151] The difference between Comparative Example 1-4 and Example 1-13 is that no filler is used;

[0152] The difference between Comparative Example 1-5 and Example 1-13 is that the amount of filler is increased, and the weight percentage of the filler is about 75.6% after conversion;

[0153] The difference between Comparative Example 1-6 and Example 1-13 is that only filler XH-SiO2-800 is used. Specific parameters are shown in Table 1-2:

[0154] Table 1-2

[0155]

[0156]

[0157] Preparation Example 3:

[0158] The preparation method of the highly breathable tape sample comprises the following steps:

[0159] Step 1: Prepare the pressure-sensitive adhesive coating liquid:

[0160] Weigh each component according to the raw material ratio of composition (2), and mix each component with a solvent to obtain a coating liquid; the solvent is ethyl acetate, and the solid content of the coating liquid is 20%.

[0161] Step 2: Coating and film forming:

[0162] The coating liquid is first coated on a release film, and after drying, is transferred to a porous PP film substrate to form a pressure-sensitive adhesive layer to obtain a highly breathable adhesive tape;

[0163] Step 3: Tape Rewinding:

[0164] A release agent is applied to the back of the porous PP film and the tape is rolled up to produce a single-sided highly breathable tape.

[0165] Preparation Example 3 corresponds to the samples of Examples 2-1 to 2-12, wherein the porosity of the porous PP film is 45±10%;

[0166] Comparative Examples 2-1, 2-2 and 2-3:

[0167] The difference between Comparative Example 2-1 and Example 2-2 is that no filler is used;

[0168] The difference between Comparative Example 2-2 and Example 2-2 is that the amount of filler is increased, and the weight percentage of the filler is about 75.3% after conversion;

[0169] The difference between Comparative Example 2-3 and Example 2-2 is that only filler XH-SiO2-800 is used. Specific parameters are shown in Tables 2-1-1 and 2-1-2:

[0170] Table 2-1-1

[0171]

[0172] Table 2-1-2

[0173]

[0174] Preparation Example 4:

[0175] The preparation method of the highly breathable tape sample comprises the following steps:

[0176] Step 1: Prepare the pressure-sensitive adhesive coating liquid:

[0177] Weigh each component according to the raw material ratio of composition (2), and mix each component with a solvent to obtain a coating liquid; the solvent is ethyl acetate, and the solid content of the coating liquid is 20%;

[0178] Step 2: Coating and film forming:

[0179] The coating liquid is first coated on a release film, and after drying, is transferred to a PP non-woven fabric substrate to form a pressure-sensitive adhesive layer to obtain a highly breathable adhesive tape;

[0180] Step 3: Tape Rewinding:

[0181] A release agent is applied to the back of the PP nonwoven fabric and the tape is rolled up to produce a single-sided, highly breathable tape.

[0182] Preparation Example 4 corresponds to samples of Examples 2-13 to 2-19;

[0183] Comparative Examples 2-4, 2-5 and 2-6:

[0184] The difference between Comparative Example 2-4 and Example 2-14 is that no filler is used;

[0185] The difference between Comparative Example 2-5 and Example 2-14 is that the amount of filler is increased, and the weight percentage of the filler is about 75.7% after conversion;

[0186] The difference between Comparative Example 2-6 and Example 2-14 is that only filler XH-SiO2-800 is used. Specific parameters are shown in Table 2-2:

[0187] Table 2-2

[0188]

[0189]

[0190] Test method:

[0191] (1) Peel strength test method - before soaking

[0192] Test method: Clean the aluminum foil to be tested with isopropyl alcohol and dry it, cut the tape sample into strips with a width of 24mm and a length of 100mm; stick the test surface of the tape strip to the aluminum foil to be tested to avoid bubbles or wrinkles, and use a 2kg pressing wheel to slowly press back and forth three times at a speed of 300mm / min; stick the back of the aluminum foil (the side without tape) to the stainless steel plate with double-sided tape, start the timer, and maintain for 20min; fix one end of the stainless steel plate on the lower fixture of the tensile testing machine and make it perpendicular to the horizontal plane, and reset the equipment; clamp the substrate of the tape strip with another fixture, and perform a peeling test at a speed of 304.8mm / min. Select a section with stable data (not shorter than 80mm) to calculate the peeling strength in N / m.

[0193] (2) Peel strength test method - after soaking

[0194] Test method: Clean the aluminum foil to be tested with isopropyl alcohol and dry it, cut the tape sample into strips with a width of 24mm and a length of 100mm, stick the test surface of the tape strip to the aluminum foil to be tested to avoid bubbles or wrinkles, and use a 2kg pressing wheel to slowly press back and forth three times at a speed of 300mm / min; start the timer and maintain for 20min; put in the electrolyte solvent (the specific composition and ratio of the electrolyte solvent are: diethyl carbonate DEC: 50%, ethylene carbonate EC: 30%, ethyl methyl carbonate EMC: 20 %) in a container that does not cover the liquid surface, seal it and bake it at 85℃ for 24hrs, then take it out and wipe off the surface solvent; stick the back of the aluminum foil (the side without tape) to the stainless steel plate with double-sided tape, start the timer and leave it for 20min; fix one end of the stainless steel plate on the lower fixture of the tensile testing machine and make it perpendicular to the horizontal plane, and reset the equipment; clamp the substrate of the tape sample with the other fixture, and perform a peel test at a speed of 304.8mm / min, and select a section with stable data (not shorter than 80mm) to calculate the peel strength, in N / m.

[0195] (3) Air permeability test method

[0196] Cut the tape sample into a circular film with a diameter of >10cm or a square film with a side length of >10cm; turn on the equipment switch, hold the slide barrel against the top of the slide barrel; rotate the slide barrel, and the infrared probe is perpendicular to the central axis of the 100ml test area; place the film to be tested on the test seat and tighten it; the screen displays "TIMER SEEKING STARTING MARK", press the "RESET" key and release the slide barrel to start the test. After the test is completed, read the value on the screen, the unit is s / 100cc. The air permeability test after soaking is to first put the cut circular film with a diameter of >10cm or a square film with a side length of >10cm into a container filled with electrolyte solvent (the specific composition and ratio of the electrolyte solvent are: diethyl carbonate DEC: 50%, ethylene carbonate EC: 30%, methyl ethyl carbonate EMC: 20%) and submerge it in the liquid surface, seal it and bake it at 85℃ for 24hrs, then take it out and wipe off the surface solvent, and then test the air permeability according to the above steps.

[0197] The test results for the above embodiments are shown in Tables 1-3, 1-4 and 2-3, 2-4, where NA means that effective testing cannot be performed:

[0198] Table 1-3

[0199]

[0200] Table 1-4

[0201]

[0202] It can be seen from Tables 1-3 and 1-4 that when composition (1) is selected, the pressure-sensitive adhesive layer containing the rubber component makes the tape have good initial air permeability, especially when the filler percentage is 40-65%, the tape can still maintain good tape air permeability after being soaked in electrolyte; considering the error situation, the peeling strength of the tape before and after soaking is very small, which overall shows that the pressure-sensitive adhesive layer has high adhesion and electrolyte stability, ensuring the long-term stable use of the tape in the battery. Among them, since comparative examples 1-1 and 1-4 do not contain fillers, comparative examples 1-2 and 1-5 have too high filler content, and comparative examples 1-3 and 1-6 only select a single particle size non-porous filler XH-SiO2-800, none of them can make the tape take into account both air permeability and adhesion. Within the appropriate range of filler dosage, embodiments 1-10 and 1-17 have low filler content, and the air permeability is slightly insufficient compared to other similar embodiments, but they can also meet most application requirements.

[0203] Table 2-3

[0204]

[0205] Table 2-4

[0206]

[0207]

[0208] It can be seen from Tables 2-3 and 2-4 that when composition (2) is selected, the pressure-sensitive adhesive layer containing a hydroxyl / carboxyl-terminated acrylic resin component makes the tape have good initial air permeability, especially when the filler percentage is 40-65%, the tape can still maintain good tape air permeability after being soaked in electrolyte; considering the error situation, the peeling strength of the tape before and after soaking is very small, which overall shows that the pressure-sensitive adhesive layer has high adhesion and electrolyte stability, ensuring the long-term stable use of the tape in the battery. Among them, since comparative examples 2-1 and 2-4 do not contain fillers, comparative examples 2-2 and 2-5 have too high filler content, and comparative examples 2-3 and 2-6 only select a single particle size non-porous filler XH-SiO2-800, none of them can make the tape take into account both air permeability and adhesion. Within the appropriate range of filler dosage, Examples 2-11 and 2-18 have low filler content, and the air permeability is slightly insufficient compared to other similar examples, but they can also meet most application requirements.

[0209] In contrast, the samples of the embodiments corresponding to composition (1) and composition (2) have good initial air permeability of the tape and bubble liquid air permeability, while the samples of the embodiments of composition (2) are overall higher in peel strength than the samples of the embodiments of composition (1). You can choose according to the specific use environment and needs.

[0210] Although preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concepts. Therefore, the present invention includes the preferred embodiments and all related changes and modifications. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. If these changes and modifications based on the present invention fall within the scope of the present invention and its equivalents, the present invention is also intended to include these changes and modifications.

Claims

1. A highly breathable adhesive tape, characterized in that: including a porous substrate and a pressure-sensitive adhesive layer; The porous substrate has a thickness of 5-50 μm and is selected from at least one of a porous polymer membrane and a non-woven fabric; The pressure-sensitive adhesive layer has a thickness of 0.5-50 μm and comprises at least one of the components (1) or (2): In terms of weight percentage, composition (1) comprises: 20-45% rubber component, 5-25% viscosity modifier, 30-75% filler, and optional tackifying resin and carbonate compound; In terms of weight percentage, composition (2) comprises: 20-70% hydroxyl / carboxyl terminated acrylate resin, 1-10% curing agent, 25-75% filler, and optional carbonate compound; The filler includes a filler with a particle size of 1nm-15μm; The filler includes a porous filler with a specific surface area of ​​2m 2 / g or more; and / or The compound filler is a small-particle filler with a particle size of 1-600 nm and a large-particle filler with a particle size of 700 nm-15 μm in a weight ratio of (20-40): (60-80); The initial air permeability of the highly air-permeable tape is less than 350s / 100cc, and the air permeability after being soaked in electrolyte is less than 370s / 100cc.

2. The highly breathable adhesive tape according to claim 1, characterized in that: The porous polymer membrane is selected from at least one of a porous PP membrane, a porous PE membrane, a porous PI membrane, a porous PAN membrane, a porous PVDF membrane, and a porous PMMA membrane, and has a porosity of 30-85%; The non-woven fabric comprises at least one of PP non-woven fabric, PE non-woven fabric, PET non-woven fabric and PTFE non-woven fabric, and the pore size is ≤10 μm.

3. The highly breathable adhesive tape according to claim 1 or 2, characterized in that: The filler is selected from at least one of boehmite, talc and silicon dioxide.

4. The highly breathable adhesive tape according to claim 3, characterized in that: In terms of weight percentage, composition (1) comprises: The rubber component is selected from at least one of SIS, SEBS, SEPS, SBR, and TPU; The viscosity modifier is selected from at least one of liquid polyolefin and naphthenic mineral oil; The tackifying resin is selected from at least one of (hydrogenated) C5 resin, (hydrogenated) C9 resin, and (hydrogenated) DCPD resin.

5. The highly breathable adhesive tape according to claim 3, characterized in that: In terms of weight percentage, composition (2) comprises: The molecular weight of the hydroxyl / carboxyl terminated acrylate resin is 20,000-500,000 Da; The curing agent is selected from at least one of multifunctional epoxy and multifunctional isocyanate.

6. The highly breathable adhesive tape according to claim 4 or 5, characterized in that: The content of the carbonate compound is 10-20%, and the carbonate compound is at least one selected from ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, and methyl propyl carbonate.

7. A method for preparing a highly breathable adhesive tape as claimed in any one of claims 1 to 6, characterized in that: The steps include: Step 1: Prepare the pressure-sensitive adhesive coating liquid: Weigh each component according to the raw material composition, and mix each component with the solvent to obtain a coating liquid; Step 2: Coating and film forming: The coating liquid is coated on a porous substrate, and dried to form a pressure-sensitive adhesive layer to obtain a highly breathable adhesive tape; or The coating liquid is first coated on a release film, and after drying, is transferred to a porous substrate to form a pressure-sensitive adhesive layer to obtain a highly breathable adhesive tape; Step 3: Tape Rewinding: A release agent is coated on the back of the porous substrate or a release film is arranged on the surface of the pressure-sensitive adhesive layer, and the tape is rolled up to produce a single-sided rolled high-air-permeable tape.

8. The preparation method according to claim 7, characterized in that: The solvent is an organic solvent, including at least one of toluene, xylene, methylcyclohexane, ethyl acetate, butyl acetate, butanone, methyl isobutyl ketone, ethanol and isopropanol, and the solid content of the coating liquid is 5-60wt%.

9. Use of the highly breathable adhesive tape according to any one of claims 1 to 6 in lithium battery pole piece protection, pole lug protection, and winding and finishing.

Citation Information

Patent Citations

  • Electrolyte-resistant lithium battery special-shaped adhesive tape and preparation method thereof

    CN117363229A

  • Laminated porous film, method for producing same, non-aqueous electrolyte secondary battery separator, laminated electrode sheet, and non-aqueous electrolyte secondary battery

    CN103946023A

  • Porous film, separator for secondary cell, and secondary cell

    CN113039069A